Dutch and Indonesian versions of the Arizona Battery for Communication Disorders of Dementia (ABCD): does the test cross boundaries of language and culture? - Dharmaperwira-Prins RII (Asia Pacific Journal of Speech, Language & Hearing, 2004)
The Arizona Battery for Communication Disorders of Dementia (ABCD), developed in the USA, was translated into Dutch and Indonesian. The Dutch translation required minor modifications; the Indonesian one required more adaptations. Four additional subtests were added to both. The Dutch ABCD was standardized on mild and moderate Alzheimer (AD) patients and normal controls; the Indonesian ABCD (IBCD) was standardized on normal controls. On subtests that discriminated most clearly between US AD patients and controls, no significant differences between US, Dutch and Indonesian norms for elderly controls were revealed. The Dutch ABCD proved to be as effective as the US ABCD in differentiating between controls and mild AD subjects. The additional Visual Memory Test in the Dutch and Indonesian versions accommodated differential diagnosis between dementia and aphasia. Adaptations and standardization results, including recent Indonesian ones, are discussed.